Stillbirths and premature births occurring in Willesden in the years 1917 to 1927 including neonatal deaths - Gray, Alice J. (The University of Edinburgh, 1930)
That Toxaemia due to morbid conditions of the mother such as Syphilis, Albuminuria , Heart, Lung and Kidney diseases is the commonest cause of Ante Natal Death.

That injury to the mother e.g., falls, etc. , are only likely to endanger the life of the ohild in the presence of some maternal or foetal disorder.

That by prom$tly treating any disease detected in the mother during pregnancy ill effects on the foetus will be prevented, such early detection and treatment constituting the first great principle in the care of the Expectant Mother. Especially is this necessary for toxaemia occurring in the first pregnancy otherwise irreparable damage may be done to the maternal tissues, so that a vicious circle is instituted in each subsequent pregnancy.

That syphilis is an important cause of ante natal death, resulting in a macerated foetus. The value of ante natal treatment in Syphilis in the reduction of stillbirths is accepted.

That injury at birth accounts for the greatest number of deaths among fresh foetuses, emphasises the fact that the less need there is for manipulative interference at its birth the greater will be the chance of the survival of the child.

That the time for interference is during the ante natal period e.g., by diagnosing and treating maipresentations.

In the neonatal deaths the princippl cause is Prematurity. Adequate ante natal care dealing with the underlying causes of prematurity may hope to reduce them by at least a proportion, although at present in a large number of cases of prematurity the cause is unknown. Reduction in this direction can be hoped for by greater and more individual bare of premature infants.

The importance of breast feeding in the rearing of the premature infant.

That the nearer to full term the premature infant is at birth, the more likely is it to live, its tissues being better able to cope with extra uterine existence.

In conclusion the reduction in the number of stillbirths and premature births can only be effected through efficient supervision of the Expectant Mother and her Unborn Child, throughout the whole of her pregnancy.